2019
DOI: 10.5334/oq.52
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Air Circulation and Hearth Location at Paleolithic Cave Sites

Abstract: Hearths were constructed and used at Paleolithic cave and rockshelter sites in Africa, Europe and Asia as early as the late Lower Paleolithic period. The advantages of the use of fire have been widely researched for the last decades. However, only a few studies have focused on the possible negative impact of the use of fire within closed spaces, such as caves. One of the major negative fire products is smoke, which has an immediate, as well as long-term, effect on humans and may even prevent cave occupation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Therefore it was impossible to conclude the measurements until the fire was extinguished, and measurements were only taken for 30 minutes. We observed that the fireplace location was not appropriately placed regarding air currents; air currents in a cave are essential to achieving a prolonged stay underground [ 1 ]. However, in the case of large fires, convection currents are produced, and they would be efficient enough to evacuate gases outside of the cave [ 3 ].…”
Section: Results: Quantitative and Qualitative Data About Paleolithic Lightingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it was impossible to conclude the measurements until the fire was extinguished, and measurements were only taken for 30 minutes. We observed that the fireplace location was not appropriately placed regarding air currents; air currents in a cave are essential to achieving a prolonged stay underground [ 1 ]. However, in the case of large fires, convection currents are produced, and they would be efficient enough to evacuate gases outside of the cave [ 3 ].…”
Section: Results: Quantitative and Qualitative Data About Paleolithic Lightingmentioning
confidence: 99%
“…The light duration restricts the time spent inside the cave and defines whether the visit will be a long stay or a short exploration. Moreover, the optimal management of some of the produced gases (i.e., the smoke of lighting tools) is essential to carry out prolonged subterranean frequentation [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we explain how the fire generated by torches or lamps affects the oxygen concentration in the cave. We start with a brief explanation of the air circulation model in caves (Kedar and Barkai 2019). We then discuss simulation experiments that measured oxygen concentration in compartments with restricted ventilation, similar to some extent to those found in a cave.…”
Section: Oxygen Ventilationmentioning
confidence: 99%
“…The height of the layers does not depend on the hall ceiling height but on the hall entrance height. Thus, the lower layer height is always lower than the entrance height (Kedar and Barkai 2019;Kedar, Kedar, and Barkai 2020).…”
Section: Oxygen Ventilationmentioning
confidence: 99%
See 1 more Smart Citation